Conversor full bridge ressonante aplicado a fontes de soldagem a arco - Barbosa, Christian Griesang (2023)
The use of power electronics in the manufacture of arc welding machines has improved many aspects of the equipment, resulting in reduced size and weight, easy handling and access to small places, for example. However, the growing industrial competitiveness and the constant search for excellence forces the study of new solutions for the permanent search for equipment reduction and power density increase. In view of this, this work presents the study, analysis, design and implementation of a resonant converter applied to arc welding sources that aims to reduce switching losses in switches. The work begins with a review of the main welding processes, presenting their particularities, followed by a review of welding sources available on the market, demonstrating their characteristics and functionalities. The static converters most used in inverter power sources are also described. A design methodology is presented which seeks to obtain smooth switching in switches, demonstrating the acquisition of resonant components and subsequent simulation through Software LTSpice in order to validate the simplified topology and the analyzed converter. Finally, the results obtained through laboratory experiments with the implementation of the analyzed converter and the comparison with the traditional Hard-Switching topology are presented.